PENGEMBANGAN LKPD LIVEWORKSHEET BERBASIS PROBLEM BASED LEARNING PADA MATERI CAHAYA (Universitas PGRI Sumatera Barat, 2022)
This research aims to develop LKPD using liveworksheets based on problem based learning on light matter. The research method used is development (research and development) with the Sugiyono development model. The results of LKPD validity have been declared very valid based on the results of validation of learning material experts obtained a value of 88% with a very valid category, and the teaching material expert obtained a value of 88% with a very valid category, and the category of all validators is very valid with a value of 83%. In addition, LKPD is stated to be very practical with a value of 88.89% without revision. Based on the response of students obtained a score of 95.25% with an excellent category. Based on the acquisition of these data, it can be concluded that LKPD using a problem-based learning liveworksheet in light matter is declared very valid and very practical to be used as an IPA teaching material in school.